Venetoclax-based regimens in octogenarian patients with CLL: efficacy, safety, and comparison to BTKi in a multicenter cohort - Andrea Serafin; Alessandro Cellini; Enrica Antonia Martino; Federica Mazzetto; Francesco Angotzi; Anna Maria Frustaci; Monia Marchetti; Riccardo Moia; Alessandro Sanna; Costantino Riemma; Francesca Cibien; Alessandro Noto; et al. (Blood Advances, 2025)
Abstract: Octogenarians represent a significant fraction of patients with chronic lymphocytic leukemia (CLL) but, despite the prevalence of the disease in this age group, limited data are available on the safety and efficacy of novel drugs in this subgroup. We conducted a multicenter retrospective study enrolling 120 octogenarian patients who received venetoclax (Ven) regimens in any line. Regarding efficacy, we found Ven to perform similarly to what is reported in younger patients with CLL, with an overall response rate of 91%, a complete response rate of 44%, and median progression-free survival of 44 months. Concerning safety, we report a toxicity profile that is consistent with previous reports, with most high-grade adverse events being of hematologic or infectious nature, given that 37% and 22% of patients experienced neutropenia or infections of grade 3 or higher. As part of our study, we compared the safety and efficacy data we collected with those obtained in a comparable Bruton tyrosine kinase inhibitor (BTKi)-treated population. We found that these 2 treatments were comparable in terms of overall efficacy, barring a higher rate of complete responses with Ven; safety profiles were different among the 2 groups given that BTKi-treated patients had more cardiovascular toxicities (26% vs 4%) and Ven-treated subjects experienced more infectious events (82% vs 49%). Our data point out that Ven-based regimens are safe and effective in octogenarian patients with CLL despite their higher clinical complexity and comorbidity burden and should provide some basis for the design of prospective studies to further evaluate the optimal treatment regimen in this patient population.